Inside China's Cities: Institutional Barriers and Opportunities for Urban Migrants - Wang, Feng; Zuo, Xuejin (American Economic Review, 1999)
One of the most glaring legacies of 20thcentury Chinese socialism is a sharp and widened divide between China's urban and rural areas. China's widened urban-rural divide arose from a socialist industrialization process, which created a hastened heavy-industrial base at the expense of its rural population. China's vast rural population not only endured a standard of living far below that in the urban sector, they were also denied access to many social welfare benefits and social-mobility opportunities (Martin King Whyte, 1996). This urban-rural gap in social and economic wellbeing, together with a massive reservoir of rural surplus labor and an acute shortage of consumer goods, formed the driving forces for China's change of migration-control policy and for the rapid increase of rural migrants in Chinese cities. Though the exact number of migrants is still hard to ascertain, due to both a lack of consensus in the definition of migrant and the absence of an authoritative national survey, migrants' prominent presence in Chinese cities is hardly disputable. In China's largest cities, for instance, it is often quoted that at least one out of every five persons is a migrant, and most likely a migrant from rural areas. In Shanghai, the number of migrants rose tenfold in one decade: from 0.26 million in 1981 to 2.81 million in 1993. The percentage of local residents who were migrants correspondingly rose from less than 5 percent in the early 1980's to 21.7 percent in 1993 (Changming Sun, 1997). In Beijing, the number of migrants was 3.29 million in 1994, compared to a locally registered population of 10.63 million for the whole municipality, and 6 million for its city districts (Dangsheng Ji et al., 1996 p. 95). In city districts, one out of every three persons in Beijing is a temporary migrant from elsewhere. Most of these recorded migrants are also genuine migrants, not short-term visitors: more than 60 percent had stayed for more than half of a year, and only 17 percent had been in Beijing for less than one month. Three-quarters of all the surveyed migrant population listed business or employment as their purpose of stay (Ji et al., 1996 pp. 96-97). Rural migrants account for over threequarters of all migrants in large Chinese cities. In Shanghai, for instance, a survey in 1995 found that 88.1 percent of all migrants had their place of household registration in the countryside (Wang and Zuo, 1997). Similarly, in Beijing, where one expects to see a higher circulation of urban to urban migrants, close to 80 percent of migrants surveyed in late 1994 were peasants before moving into Beijing (XiuhuaLiu, 1996 p. 112).